Use of Open Source Software in Health Care Delivery – Results of a Qualitative Field Study - Schmuhl, H.; Heinze, O.; Bergh, B. (Yearbook of Medical Informatics, 2013)
Objectives: To assess and analyze the attitude of health IT executives towards the utilization of specialized medical Open Source software (OSS) in Germany's and other European countries' health care delivery.Methods: After an initial literature review a field study was carried out based on semi-structured expert interviews. Eight German and 11 other European health IT executives were surveyed. The results were qualitatively analyzed using the grounded theory approach. Identified concepts were reviewed using SWOT analysis.Results: In total, 13 strengths, 11 weaknesses, 3 opportunities, and 8 threats of the utilization of OSS in a clinical setting could be identified. Additionally, closely related aspects like general software procurement criteria, the overall attitude of health IT executives, users, and management towards OSS and its current and future use could as well be assessed.Conclusions: Medical OSS is rarely used in health care delivery. In order to capitalize the unique advantages of OSS in a clinical setting, complex requirements need to be addressed. Shortcomings of OSS describe an attractive breeding ground for new commercial offerings and services that need yet to be seen.
Keywords: Open source; software; qualitative survey; health care delivery; health information technology; free software